The underestimated benefits of descriptive representation and gender quotas - Espírito-Santo, Ana; Verge, Tània; Wiesehomeier, Nina (114th APSA Annual Meeting and Exhibition, 2018)
While there is a broad debate in the literature on whether descriptive representation improves substantive representation, other benefits that descriptive representation may bring about have received considerable less attention. As argued by Mansbridge (1999), the representation of historically under‐represented groups might have two important benefits: (i) it might help the under‐represented group construct social meaning, i.e. to improve the way the society as a whole evaluates the group’s capacity of ruling; and (ii) it might contribute to achieving a de facto legitimacy, by making members of those groups feel as if they themselves were present in the deliberations. Although Mansbridge’s theory has been vastly quoted, to our knowledge, it has never been empirically tested at the individual level. Do citizens perceive these benefits? And how might this perception be affected when increases in descriptive representation are achieved through a widely used but still contested measure like quotas? In answering those questions we focus on women’s representation and draw on data from an online framing experiment, administered in 2015 to a nationally representative sample of the population in both Spain and Portugal. In particular, we analyse whether random assignment to two dissimilar treatment conditions – a scenario where gender quotas are mentioned and another one where they are not mentioned – or to the control group (no treatment) reveals differences in the perceived benefits of descriptive representation.